THE USE OF PADLET IN COLLABORATIVE WRITING IN BIPA 2 CLASS - Khoirunnisa, Ananda Siti; Kurniawan, Khaerudin (Universitas Negeri Makassar, 2025)
The teaching of writing in a foreign language requires engaging approaches to foster learners’ motivation and participation. This study explores the integration of the Padlet platform in collaborative writing activities within the Bahasa Indonesia bagi Penutur Asing (BIPA) classroom context. This study employed a mixed-methods design, collecting data from writing assessments (pre-test and post-test), questionnaires, observations, and field notes. Fifteen learners are involved in an online BIPA 2 course. Quantitative data were analyzed using a Paired T-Test in SPSS, while qualitative data were examined through Miles and Huberman’s interactive model. The findings indicate that the application of collaborative writing strategies using Padlet facilitated active learner engagement and produced notable improvements in writing quality. Learners demonstrated increased idea exchange and creativity, as evidenced by a rise in average scores from the pre-test to the post-test. This study provides pedagogical insights for BIPA teachers in enhancing writing instruction through the use of digital collaboration tools.